Psychological factors influencing motivation, cooperation, participation, satisfaction, self appraisal, and individual quality of life in adolescents and adults undergoing Orthodontic treatment - Pawar, Oshin; Joneja, Purva; Choudhary, Deepak Singh (Orthodontic Journal of Nepal, 2021)
Introduction: To bring the best outcome from both the sides i.e. the orthodontist and the patient , it is of prime importance to understand certain psychological factors, and to treat every patient with an individualistic approach. The need was to study all such psychological factors and to find a method to deal with the same; to evaluate the psychological factors that influences the self appraisal and individual Quality of life. To compare psychological factor affecting the self appraisal and individual quality of life before treatment and after treatment, to study psychological factors of patients which influences the treatment outcome and to find a method to manage them. Materials and Method: This In-vivo study, includes case study and survey. Two separate sets of questionnaires (before and after undergoing orthodontic treatment) were given to patients. The study also included psychological test scales like OHIP-14 and 12-CSES. The sample size of patient was 150. Result: The study revealed that esthetics (95%) is the main concern for getting treatment especially for female (56%). There is improvement in OHIP and CSES (interval of 12.63, 14.66) score of patients before and after treatment. Patients’ satisfaction (94.7%) increases on having healthy orthodontist-patient relationship. Conclusion: Esthetics is the main concern. Most patients wants improvement in smile. Lack of awareness and lack of financial supports is the main reason for delay in getting treatment. The main discomfort about the treatment reported by participants was pain after activation appointments, ulcers and change in food eating habit. The orthodontic therapy improves confidence, satisfaction, individuals’ appraisal and quality of life. There were no variations in response for patients’ satisfaction by gender, age, education or by treatment duration.